2004
DOI: 10.2174/1570162043485077
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T-Cells: Function and Response to HIV Infection

Abstract: CD8+ T-cells are a critical component of the cellular immune response and they play an important role in the control of viral infection. During HIV infection, CD8+ T-cells are able to recognize infected cells through an MHC-I dependent process and are able to lyse cells harboring viral infection by the secretion of perforin and granzymes. These cytotoxic T-lymphocytes (CTL) can also eliminate virally infected cells through the engagement of death-inducing ligands expressed by CD8+ T-cells with death receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
94
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 208 publications
0
94
0
6
Order By: Relevance
“…Overall, our findings suggest that other mechanisms may have contributed to the reestablishment of the control of infection in these macaques. CD8 ϩ T cells can inhibit HIV/SIV infection through noncytolytic soluble factors (47). Several reports have suggested that these mechanisms may play a major role in the CD8-mediated partial control of SIV infection during primary infection in macaques (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our findings suggest that other mechanisms may have contributed to the reestablishment of the control of infection in these macaques. CD8 ϩ T cells can inhibit HIV/SIV infection through noncytolytic soluble factors (47). Several reports have suggested that these mechanisms may play a major role in the CD8-mediated partial control of SIV infection during primary infection in macaques (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…In HIV infection, decreased CD8+ counts are associated with immune deficiency (Gulzar and Copeland, 2004), correlated with the absence of submandibular/ sublingual saliva (Mulligan et al, 2000), and the resulting opportunistic infections in the oral cavity (Fidel, 2006). A recent study demonstrated a significant correlation between CD8+ T-cell activation levels and total bacterial 16S rDNA present in stool samples of HIV+ individuals (Ellis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…+ T cells and macrophages secrete these soluble factors, which then inhibit HIV-1 replication in a non-cytolytic fashion (Gulzar & Copeland, 2004).…”
Section: Genetic Factorsmentioning
confidence: 99%